Analysis of Plant Watering Efficiency Using IoT Technology Controlled Through Google Assistant - Nur Hakim; Muhammad Hazmi; Syam Gunawan; Arnes Yuli Vandika; Hanifah Nurul Muthmainah (Westscience Press, 2024)
This paper presents a systematic literature review (SLR) of 120 academic documents sourced from the Scopus database, which analyses the efficiency of crop watering systems utilizing Internet of Things (IoT) technology controlled via Google Assistant. The review explores key advances in IoT-based irrigation systems, highlighting how real-time data from sensors and voice-controlled automation improve water efficiency and user experience. The findings reveal that IoT systems can reduce water wastage by 25-30%, optimise plant health, and offer convenience through voice commands. However, challenges such as connectivity issues, high implementation costs, and system maintenance complexity also need to be addressed. This paper discusses potential future research directions, including scalability, AI integration, and cost-effective solutions to expand the adoption of these technologies in agriculture and horticulture.